Studies on Seed Germination in Capparis decidua (Forsk.) Edgew : a Tree of Hot Desert - Kumar, Devendra; Mishra, Dhruv Kumar (Indian Forester, 2008)
Pre-germination treatments applied to seeds of Capparis decidua were evaluated for alleviation of dormancy. Response to treatments provided evidence as to the type of dormancy and suitable pre-sowing treatment to enhance germination. The extract of whole seed and the embryo significantly reduced mean germination time of wheat seeds.